Analisis Penggunaan Gaya Bahasa Pada Puisi “Cinta Sebatas Rindu” Karya Okto Son - Sinti Luthfia Redina (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This study aims to analyze the use of figurative language in Okto Son's poem "Cinta Sebatas Rindu". This poem was chosen because of its strong aesthetic and emotional appeal, and this study aims to understand how language style is used to convey messages and emotions in the poem. The main problem to be answered in this study is how Okto Son uses the style of language in the poem Cinta Selimit Rindu to create an in-depth reading experience and how to use that style of language. The research method used is qualitative. This poem will be analyzed in depth with a focus on the use of figurative language such as similes, symbols, personification, repetition and similes. The benefit of this research is to provide a better understanding of the use of figurative language in poetry. It is hoped that the results of this study will reveal a variety of figurative language strategies used by Okto Son and how the use of figurative language creates strong aesthetic and emotional experiences for readers. This analysis can also help explore hidden meanings in poetry and reveal the uniqueness of Okto Son's writing style.